CITIZENSHIP IN SCIENCE INTEGRATED SCIENCE, TECHNOLOGY, SOCIETY: MIDDLE SCHOOL TEACHERS' PERCEPTIONS OF LEARNING TOOLS - Septi, Sabila Eka; Asrial, Asrial; Damris, Damris (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2025)
This study aims to analyze teachers' perceptions of the development of Citizenship-based learning devices in science integrated with the Science, Technology, and Society approach to make students have critical thinking skills, science process skills, and students' curiosity in learning energy material. A mixed method approach was used, combining qualitative and quantitative data. The study involved five schools, with qualitative data obtained through teacher interviews and classroom observations, while quantitative data were collected through teacher perception questionnaires. The findings showed that the developed devices were positively received and considered effective in making students have critical thinking skills, science process skills, and students' curiosity in learning energy material and can connect scientific concepts with social and environmental issues. Furthermore, the devices were found to support the development of scientific attitudes and awareness of the social impacts of science and technology. Overall, the learning devices were considered suitable for contextual and meaningful science education